2006
DOI: 10.1890/0012-9615(2006)076[0461:mpotsi]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Mosaic Patterns of Thermal Stress in the Rocky Intertidal Zone: Implications for Climate Change

Abstract: Abstract. We explicitly quantified spatial and temporal patterns in the body temperature of an ecologically important species of intertidal invertebrate, the mussel Mytilus californianus, along the majority of its latitudinal range from Washington to southern California, USA. Using long-term (five years), high-frequency temperature records recorded at multiple sites, we tested the hypothesis that local ''modifying factors'' such as the timing of low tide in summer can lead to large-scale geographic mosaics of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
360
1
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 437 publications
(376 citation statements)
references
References 85 publications
12
360
1
3
Order By: Relevance
“…Thus, the M. parksii zone may eventually collapse to zero (a local extinction event) as conditions warm through time, as has been observed across local and regional scale temperature gradients in space (8). Furthermore, in the southern portions of its range, or at localized ''hotspots'' (23,24), site-scale local extinctions should become more frequent, resulting in step-like range contractions that reflect the stochastic occurrence of lethal stress events. Although the ''tipping point'' and the mechanisms underlying the responses of this high intertidal alga may seem minor on a global scale, they clearly identify the challenge to managers of anticipating, let alone reacting to more catastrophic events.…”
Section: Resultsmentioning
confidence: 92%
“…Thus, the M. parksii zone may eventually collapse to zero (a local extinction event) as conditions warm through time, as has been observed across local and regional scale temperature gradients in space (8). Furthermore, in the southern portions of its range, or at localized ''hotspots'' (23,24), site-scale local extinctions should become more frequent, resulting in step-like range contractions that reflect the stochastic occurrence of lethal stress events. Although the ''tipping point'' and the mechanisms underlying the responses of this high intertidal alga may seem minor on a global scale, they clearly identify the challenge to managers of anticipating, let alone reacting to more catastrophic events.…”
Section: Resultsmentioning
confidence: 92%
“…This is perhaps surprising because studies have shown that such differences in seawater temperatures can influence the reproductive ability of benthic marine invertebrates (Brey 1995, Vilchis et al 2005, and field investigations have detected reduced fecundity at range limits due to changes in seawater temperature (Barber & Blake 1983, Amaro et al 2005). However, Helmuth et al (2006) assessed body temperatures of the intertidal mussel Mytilus californianus across a latitudinal gradient in sea-surface temperatures and found that body temperatures were often hotter or colder than was predicted from sea-surface temperatures. Consequently, the lack of a latitudinal decline in larval production within the present study may reflect complex interactions between air and seasurface temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…Northward range shifts in the distribution of marine organisms, such as the Zebra perch fish, Hermosilla azurea (Sturm & Horn, 2001), and the Kellet s whelk, Kelletia kelletii (Zacherl et al, 2003), have already been measured in California. Other studies have identified the presence of hotspots and coldspots where maximal and minimal daily temperatures are relatively higher and lower, respectively, than expected at their latitudes (Helmuth et al, 2006). Intertidal organisms in these regions are susceptible to temperatures outside their normal physiological range which may result in lethal alterations of biological and physiological processes (Stillman, 2002), since almost all biological structures and processes are affected by temperature (Hochachka & Somero, 2002).…”
Section: Crustacean Research 46mentioning
confidence: 99%